Cardiometabolic Effects of Postnatal High-Fat Diet Consumption in Offspring Exposed to Maternal Protein Restriction In Utero - Simões-Alves, Aiany Cibelle; Arcoverde-Mello, Ana Paula Fonseca Cabral; Campos, Jéssica de Oliveira; Wanderley, Almir Gonçalves; Leandro, Carol Virginia Gois; da Costa-Silva, João Henrique; de Oliveira Nogueira Souza, Viviane (Frontiers in Physiology, 2022)
In recent decades, the high incidence of infectious and parasitic diseases has been replaced by a high prevalence of chronic and degenerative diseases. Concomitantly, there have been profound changes in the behavior and eating habits of families around the world, characterizing a “nutritional transition" phenomenon, which refers to a shift in diet in response to modernization, urbanization, or economic development from undernutrition the excessive consumption of hypercaloric and ultra-processed foods. Protein malnutrition that was a health problem in the first half of the 20th century has now been replaced by high fat diets, especially diets high in saturated fat, predisposing consumers to overweight and obesity. This panorama points us to the alarming coexistence of both malnutrition and obesity in the same population. In this way, individuals whose mothers were undernourished early in pregnancy and then exposed to postnatal hyperlipidic nutrition have increased risk factors for developing metabolic dysfunction and cardiovascular diseases in adulthood. Thus, our major aim was to review the cardiometabolic effects resulting from post-natal hyperlipidic diets in protein restricted subjects, as well as to examine the epigenetic repercussions occasioned by nutritional transition.